PENGARUH PAJAK, TUNNELING INCENTIVE DAN GOOD CORPORATE GOVERNANCE (GCG) TERHADAP INDIKASI MELAKUKAN TRANSFER PRICING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2016-2019 - Sizka Zola Amarta; Noor Shodiq Askandar; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACT This study aims to determine the Effects of Tax, Tunneling Incentive and good corporate governance on Transfer Pricing Decisions. The population in this study is manufacturing companies listed on the Indonesia stock exchange. The sampling technique is a purposive sampling technique, the selected sample is 24 companies. Data retrieved using the documentation method. The data analysis method is multiple regression analysis with SPSS software version 14 (Product and Service Statistics solution version 14). The test data used is the simultaneous hypothesis test (f), the coefficient of determination (R2), and the partial hypothesis test (t). The results showed that simultaneous independent variables significantly influence the dependent variable. Based on the results of the coefficient of determination test, the adjusted R value is 62,8% while the remaining 0,372% is influenced by other variables not included in this study. Based on the results of partial tests that the variable tax, tunneling incentives and good corporate governance affect transfer pricingKeywords : Tax, Tunneling Incentive, good corporate governance and Transfer Pricing